Feudal Culture in the Ijen Highlands’ Poor Society - Latifatul Izzah (Institut Agama Islam Negeri Madura, 2016)
This study aims to respond the problems on: Why Indonesia which is merely independent but there still exists the feudal culture in the society, especially people around the Ijen highlands? The problem is investigated along several questions, elaborated as: 1) What causes PT. Nusantara Plantation XII (PTPN XII) gains HGU (Cultivation Right on Land) from the government to manage the coffee plantations in the Ijen highlands?; 2) Why people around the Ijen highlands only became workers in their own homes? This research combines the historical and anthropological political methods, particularly the use of agricultural involution theory and the theory of hegemony to examine why the feudal culture still exist among the already independent society, especially in the Ijen highlands. The results of this study are: (1) PTPN XII got HGU of the government to manage the coffee plantations in the Ijen highlands is not merely without a reason, but it has gone along a careful govern-ment consideration. PTPN XII is a state-owned company managed by a profes-sional so that the government benefited from a big share of profit in every single year. (2) the society of the Ijen Highland became laborer in their own homes is because the large number of people work for PTPN XII, particularly in Blawan and Kalisat Jampit plantations, as laborers not as skilled employees.Copyright (c) 2016 by KARSA. All right reserved DOI: 10.19105/karsa.v24i2.1129